Stereotyped Combination of Hearing and Wind/Gravity-Sensing Neurons in the Johnston’s Organ of Drosophila - Ishikawa, Yuki; Fujiwara, Mao; Wong, Junlin; Ura, Akari; Kamikouchi, Azusa (Frontiers in Physiology, 2020)
The antennal ear of the fruit fly, called the Johnston’s organ (JO), detects a wide variety of mechanosensory stimuli, including sound, wind, and gravity. Like many sensory cells in insect, JO neurons are compartmentalized in a sensory unit (i.e. scolopidium). To understand how different subgroups of JO neurons are organized in each scolopidial compartment, we visualized individual JO neurons by labeling various subgroups of JO neurons in different combinations. We found that vibration- (or deflection-) sensitive neurons rarely grouped together in a single scolopidial compartment. This finding suggests that JO neurons are grouped in stereotypical combinations each with a distinct response property in a scolopidium.